Sexual deviance and society a sociological examination - Worthen, Meredith G. F. (bingdon, Oxon Routledge, 2016)
"In a society where sexualized media has become background noise, we are　frequently discouraged from frank and　open discussions about sex and　offered few tools for understanding sexual behaviors and sexualities that are perceived as being out of the norm. This book encourages readers to establish new ways of thinking about stigmatized peoples and behaviors, and to think critically about gender, sex, sexuality and sex crimes" -- Provided by publisher.
Introduction and self-care -- Unit I: Sociology of deviance and sexuality -- Defining deviance -- Theories of crime and deviance -- Social power and gender, sex, and sexuality -- Gender and deviance / Meredith G. F. Worthen and Danielle Dirks -- Unit II: Sexual deviance -- Defining sexual deviance -- Historical perspectives on sexual deviance -- Adolescent sexual deviance / Amanda E. Fehlbaum -- Unit III: Deviant sexual acts -- Sex in public -- Fetishes -- Sex work / Chauntelle A. Tibbals -- Unit IV: Sex crimes and criminals -- Rape and sexual assault -- Sex crimes against children / Melissa S. Jones -- Sex offenders and society -- Concluding remarks -- Glossary.
The right of Meredith G.F. Worthen to be identified as author of this work has been asserted by her in accordance with sections 77 and 78 of the Copyright, Designs and Patents Act 1988.
Includes bibliographical references and index.
Keywords: Paraphilias; Sex crimes; Public sex